Insya' Textbook Design to Improve Writing Skills for Class IV Regular & III Intensive TMI Al-Amien Prenduan Students - Maghfirotul Hasanah; Abdul Hafidz Bin Zaid; Agus Yasin; Lailatul Barokah; Aufal Muhammad Safii (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This research comes from a special Insya' book design which according to many academics and previous research is effective and able to improve students' writing skills. This research uses the R&D method, namely a combination of qualitative and quantitative. The qualitative segment involves observation, interviews and literature review. Observations were carried out to review how teachers applied the Insya' textbook and how students understood the material they had learned from the Insya' textbook. The quantitative aspect was carried out to determine the effectiveness and suitability of Insya' textbooks which have been designed using Non Parametric T-Test analysis, namely the Wilcoxon Test because the values ​​are not normal and not homogeneous. This research included 60 Class IV Regular & III Intensive TMI Al-Amien Prenduan Students, namely 20 students for the first Pre-Test & Post-Test and 40 for the second or wider Pre-Test & Post-Test. The results show an increase in students' writing skills with an achievement of 20% from the Pre-Test (5.50) & Post-Test (7.68). Therefore, the Insya' book design is effective for use in learning to improve students' writing skills. These results are in accordance with the results obtained from previous research, namely a significant increase in students' writing skills by designing a special Insya' textbook. Researchers recommend further development of Insya' textbooks, especially to improve students' writing skills, especially development of the material or teaching materials that students will study.